Crescimento e produtividade da soja e progresso de ferrugem asiática em diferentes condições de disponibilidade de nitrogênio - Ramos, Juliano Perlin de (2014)
The objective of this work was to determine the effect of mineral nitrogen fertilization rates on nodulation, plant growth, yield and the effect of nitrogen rates on the progress of Asian soybean rust (Phakopsora pachyrhizi Sydow) of two short cycle soybean cultivars. Experiments were carried out in greenhouse and in the field, in 2011/12 and 2012/13. In the greenhouse, plants were grown in sand and supplied with five nutrient solutions and also grown in a mixture of sand plus soil and supplied by six mineral nitrogen rates. In the field, plants were fertilized with six mineral nitrogen rates. For determinations of Asian soybean rust, experiments were doubled and Phakopsora pachyrhizi was inoculated. In all experiments, active nodules, growth, grain yield and plant N concentration was determined. In Asian soybean rust experiments, defoliation and the area under rust progress curve (AURPC) was determined. In the field, nitrogen rates increased plant growth only in 2011/12. Active nodules per plant decreased in all experiments. Grain yield was not affected by N rates in the field. In the greenhouse, nitrogen rates increased plant growth and the disease progress. In 2011/12 field experiment, a slight decrease of rust progress and a slight increase in yield was recorded. Mineral nitrogen fertilization can increase plant growth and grain yield under optimal supply of water and nutrients. However, under favorable environmental conditions for the Asian rust, the increase in grain yield by effect of high N rates might not be attained due to the damage caused by the disease.